Long-term follow-up of a patient undergoing interatrial shunt device implantation for treatment of heart failure with a preserved ejection fraction - Libor Dujka; Petr Neužil; Vivek Reddy; Martin Mates; Tomáš Mráz; Jiří Weichet; Jan Komtebedde; Filip Málek (Journal of International Medical Research, 2022)
We herein present a case study of a patient with heart failure with a preserved ejection fraction and severe symptoms who underwent interatrial shunt device implantation and follow-up at a tertiary care heart failure clinic. The interatrial shunt device implantation was successful. No adverse events occurred, and the device prevented hospitalization for heart failure during long-term follow-up.